Regional cooperation: Key to climate change adaptation in HKH region (Nepal Journal of Environmental Science, 2013)
Hind Kush Himalayan (HKH) region is shared by eight countries namely: Afghanistan, Bangladesh, Bhutan, China, India, Myanmar, Nepal and Pakistan, and extends nearly east-west direction covering about approximately 3500 km. Since the region has both the fastest growing economy and the poorest countries, regional cooperation has become a necessity to sustain current rate of economic growth, continue with the efforts for poverty reduction, and meeting the challenges of achieving the millennium development goals (MDG) against the backdrop of climate change, to which the region is quite vulnerable. The average temperature in the HKH region is rising with changes in precipitation occurring across the region. The impact of climate change has been felt across the region, beyond national boundaries. Droughts, flash floods, and torrential rains in Afghanistan; glacial lakes outburst floods in Nepal; rapid glacier melting in Bhutan; flooding, and cyclones in Bangladesh; temperature rise and declining ground water table in India; and flooding in Pakistan are in increasing trend. This situation calls for a joint collaborative initiatives at the regional level to make and implement effective adaptation measures in order to protect fragile mountain ecosystem and age-old tradition and practices for sustainable development of region. There are two major barriers related to adaptation and governance issues, which under certain circumstance also need regional cooperation to solve. Since China and India are the fastest growing economic powers, it is high time that they take a collective lead role and the rest of the countries share ...